2022
DOI: 10.1177/11206721221083722
|View full text |Cite
|
Sign up to set email alerts
|

Functionally significant polymorphisms of the MMP9 gene are associated with primary open-angle glaucoma in the population of Russia

Abstract: Purpose The aim of this study was to investigate the role of functionally significant loci of the matrix metalloproteinases genes 1, 3, 9 ( MMP1, MMP3, and MMP9) in the development of primary open-angle glaucoma (POAG) in Caucasians of the Central region of Russia. Methods In total 604 participants were recruited for the study, including 208 patients with POAG and 396 healthy controls. They were genotyped at eight single nucleotide polymorphisms (SNPs) of the three MMP genes. The association was analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…One meta-analysis suggested that rs1799750 is associated with a risk of developing PACG and XFG [ 123 ]. In addition to the increased risk of POAG, Ponomarenko et al [ 126 ] reported that rs1799750 is related to earlier onset of POAG development. However, Mossböck et al [ 127 ] reported that G was not associated with POAG and XFG development in Caucasians.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One meta-analysis suggested that rs1799750 is associated with a risk of developing PACG and XFG [ 123 ]. In addition to the increased risk of POAG, Ponomarenko et al [ 126 ] reported that rs1799750 is related to earlier onset of POAG development. However, Mossböck et al [ 127 ] reported that G was not associated with POAG and XFG development in Caucasians.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on rs3918249 have reported a decreased risk of glaucoma [ 126 , 131 , 132 ]. A reduced risk of POAG has been reported in the Russian population [ 126 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations